Juragan, Kiai dan Politik di Madura - Imam Zamroni (Universitas Islam Indonesia, 2007)
This research aims to describe the Juragan, Kijaji and Politics in Madura. The existence of local elites is always identified with many social influences that they have in many aspects. So does the Juragans as economic elites, whith the amount of wealth, having a great influence in society. It had also been the case in local political activities in the post Soeharto era, that the Juragan and Kijaji tried to struggle political power in government using their richness, as primary capital. They tried to invest their capitals by participating in a certain political party to occupy strategic positions either in the village or regional levels. An effort building connections with others local elites becomes one of political strategies in occupying structural powers in order to strengthen their social positions. Keywords: Capital, politics, power.